ASSESSMENT OF TOTAL PETROLEUM HYDROCARBONS (TPH) CONTAMINATION WITH Kyllinga pumila And Spirogyra longata AROUND NIGERIAN NATIONAL PETROLEUM CORPORATION (NNPC) JOS DEPOT’S EFFLUENT WATER DISCHARGED POINT (FUDMA JOURNAL OF SCIENCES, 2021)
One of the major environmental problems today is hydrocarbons contamination resulting from activities related to the petrochemical industry. Accidental releases of petroleum products are of particular concern in to the environment hydrocarbons compounds have been known to belong to the family of carcinogenic and neurotoxin organic pollutants. The use of plants to clean up this contaminated site is a promising technology and the ability of the plants to germinate and grow in petroleum-contaminated soil differs due to plants species as well as petroleum hydrocarbons types. In this study, total petroleum hydrocarbons (TPH) were determined in Kyllinga pumila and Spirogyra longata growing at Nigerian national petroleum corporation (NNPC) Jos Depot. The chemical analysis was carried out with the aid of Gas Chromatography and Mass Spectrometry (GC-MS) detector, the result showed that Spirongyra longata could germinate and grow in petroleum products contaminated site with TPH level of 6881.98595 ppm and Kyllinga pumila did not survived in the same site with TPH level of 9536. 88801 ppm.
Keywords: Total petroleum hydrocarbons (TPH), plants and environmental contamination